Domestic Violence on the Italian Screen: Representation and Resistance - Luciano, Bernadette (Violence against women, 2023)
This article looks at how contemporary Italian films address issues of the tragedy and horror of domestic abuse and attempt to create a space for reflection and change. Ferzan Ozpetek's (2008) Un giorno perfetto (A Perfect Day), Andrès Arce Maldonado's (2017) Dentro (Inside), and Ivano De Matteo’s (2016) La vita possibile (A Possible Life) ultimately challenge the perception of domestic violence as a fixed and unchangeable condition for women. The films explore how female solidarity, empathy, and care can serve as pathways to combatting the isolation, guilt, and associated emotions that prevent women from seeking or finding la vita possibile.